The United States’ Interest in the Guaraní Aquifer in Paraguay - Tamayo Belda, Eduardo (Journal of Leadership, Accountability and Ethics, 2021)
The control and extraction of natural resources throughout the world —like water— is part of the global strategy of the United States of America in order to maintain a hegemonic position in the commodities market in energy, agriculture or mining exploitation sectors. This text studies the United States interests and those of global companies supported by them in relation to the water resource located in Paraguayan territory called Guaraní Aquifer (being of high geostrategic importance); it also analyzes the current national Paraguayan regulation that can guarantee the public ownership and management of water, avoiding the penetration and preponderance of private or foreign interests.